2020
DOI: 10.1149/1945-7111/ab8b00
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fluorine Doping on Nickel-Rich Positive Electrode Materials for Lithium-Ion Batteries

Abstract: Three fluorine-doped lithium nickel oxide samples series (LiNiO2−xFx, LiNi1−xMgxO2−xFx; Li1+x/2Ni1−x/2O2−xFx) were prepared and investigated. It is suggested that fluorine was introduced into the lattice structure during the calcination. As fluorine is introduced into LiNiO2−xFx and LiNi1−xMgxO2−xFx the percentage of Ni (or Ni and Mg) in the Li layer increases for x > 0.05. However, adding excess Li in Li1+x/2Ni1−x/2O2−xFx sucessfully balances the charge differential introduced by fluorine doping therefore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 42 publications
0
27
0
Order By: Relevance
“…39 Recently, by means of XRD, Rietveld refinement, and pH titration, Dahn et al showed fluorine is being introduced into the lattice of high-nickel materials. 34 They observed an increase in the a and c parameters along with reduction in particle size after fluorination. In our study, no significant changes in the lattice parameters are observed, indicating that fluorine is not significantly doping into the lattice but rather stays on the surface due to the low enough calcination temperature (400 °C) with NH 4 F. The presence of fluorine at the surface was further confirmed by STEM energy-dispersive X-ray spectroscopy (EDS) mapping and line scanning (Figure S2).…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…39 Recently, by means of XRD, Rietveld refinement, and pH titration, Dahn et al showed fluorine is being introduced into the lattice of high-nickel materials. 34 They observed an increase in the a and c parameters along with reduction in particle size after fluorination. In our study, no significant changes in the lattice parameters are observed, indicating that fluorine is not significantly doping into the lattice but rather stays on the surface due to the low enough calcination temperature (400 °C) with NH 4 F. The presence of fluorine at the surface was further confirmed by STEM energy-dispersive X-ray spectroscopy (EDS) mapping and line scanning (Figure S2).…”
Section: Resultsmentioning
confidence: 93%
“…With XRD and 7 Li as well as 19 F magic-angle spinning (MAS) nuclear magnetic resonance (NMR) spectroscopy, Croguennec et al suggested that fluorine does not get doped into the structure by substituting oxygen but stays as small LiF particles at the grain boundaries . Recently, by means of XRD, Rietveld refinement, and pH titration, Dahn et al showed fluorine is being introduced into the lattice of high-nickel materials . They observed an increase in the a and c parameters along with reduction in particle size after fluorination.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[11] Hence, concerns have been expressed about its electrochemical [12][13][14] and thermal [15,16] performance especially at high degrees of delithiation (> 4.3 V vs. Li/Li + ). Although extensive works [17,18] have shown that cation-substituted Ni-rich cathodes, e. g., LiNi 1-x-y Mn x Co y O 2 (1-x-y � 0.8), can improve the structural/thermal stability and cyclability, the renaissance of research interest in LiNiO 2 has been underway, [19][20][21][22][23] to meet the harsher criteria for EVs batteries. [1,2] Among the challenges such as parasitic surface reactions [24,25] and formation of disordered rock-salt (NiO) impurity [26,27] at high state-of-charge (SOC), the sequential phase transition (H1-M-H2-H3) [28,29] might play a more profound role in altering the structural stability.…”
Section: Introductionmentioning
confidence: 99%
“…The XRD patterns and Rietveld refined results of different samples are shown in Figure and Table . According to Figure a, three samples of P-LNCM83, W-LNCM83, and Aq-LNCM83@CPPO all have a α-NaFeO 2 type layered structure, and the diffraction peaks of the impurities are not observed in the diffraction pattern of the three samples. What’s more, from the enlarged diffraction peak of (003) and (104) planes, it is found that the W-LNCM83 and Aq-LNCM83@CPPO samples’ peak positions are slightly shifted to the left side compared to that of P-LNCM83.…”
Section: Resultsmentioning
confidence: 99%